Deuterated reagents in multicomponent reactions to afford deuterium-labeled products - Schofield, Kevin; Maddern, Shayna; Zhang, Yueteng; Mastin, Grace E.; Knight, Rachel; Wang, Wei; Galligan, James; Hulme, Christopher (Beilstein Journal of Organic Chemistry, 2024)
The utility of bio-isosteres is broad in drug discovery and methodology herein enables the preparation of deuterium-labeled products is the most fundamental of known bio-isosteric replacements. As such we report the use of both [D1]-aldehydes and [D2]-isonitriles across 8 multicomponent reactions (MCRs) to give diverse arrays of deuterated products. A highlight is the synthesis of several FDA-approved calcium channel blockers, selectively deuterated at a t1/2 limiting metabolic soft-spot via use of [D1]-aldehydes. Surrogate pharmacokinetic analyses of microsomal stability confirm prolongation of t1/2 of the new deuterated analogs. We also report the first preparation of [D2]-isonitriles from [D3]-formamides via a modified Leuckart–Wallach reaction and their use in an MCR to afford products with [D2]-benzylic positions and likely significantly enhanced metabolic stability, a key parameter for property-based design efforts.
Keywords: deuterated aldehydes; deuterated formamides; deuterated isocyanides; DHPs; kinetic isotope effect; Leuckart–Wallach; microsomal stability; multicomponent reactions